Research methods in language attitudes - Kircher, Ruth 1979-; Zipp, Laura 1978- (Cambridge, United Kingdom Cambridge University Press, 2022)
"Attitudes towards spoken and written language are of significant interest to researchers in sociolinguistics, applied linguistics, communication studies, and social psychology. This is the first interdisciplinary guide to traditional and cutting-edge methods for the investigation of language attitudes. Written by experts in the field, it provides an introduction to attitude theory, helps readers choose an appropriate method, and guides through research planning and design, data collection, and analysis. Chapters include step-by-step instructions to illustrate and facilitate the use of the different methods as well as case studies from a wide range of linguistic contexts. The book also goes beyond individual methods, offering guidance on how to research attitudes in multilingual communities, in signing communities, based on historical data, with the help of priming, and by means of mixed-methods approaches"-- Provided by publisher.
An introduction to language attitudes research / Ruth Kircher and Lena Zipp -- Analysis of the societal treatment of language. Discourse analysis of print media / Olivia Walsh -- Content analysis of social media / Mercedes Durham -- Discourse analysis of spoken interaction / John Bellamy -- Analysis of communication accommodation / Jakob Leimgruber -- Variable analysis / James Hawkey -- Direct methods of attitude elicitation. Semi-structured interviews / Petros Karatsareas -- Focus groups / Michael Hornsby -- Questionnaires to elicit quantitative data / Ruth Kircher -- Questionnaires to elicit qualitative data / Lena Zipp -- Perceptual dialectology / Chris Montgomery -- Indirect methods of attitude elicitation. The matched-guise technique / Verónica Loureiro-Rodríguez and Elif Acar -- The Verbal-Guise Technique / Marko Dragojevic and Sean Goatley-Soan -- The theatre-audience method / Tore Kristiansen -- Experimental methods to elicit language attitudes among children / Jasmine M. DeJesus, Radhika Santhanagopalan, and Katherine D. Kinzler -- The Implicit Association Test paradigm / Laura Rosseel -- Overarching issues of language attitudes research. Researching language attitudes in multilingual communities / Bernadette O'Rourke -- Researching language attitudes in signing communities / Annelies Kusters, Maartje De Meulder, and Erin Moriarty -- Researching language attitudes based on historical data / Anna D. Havinga and Andreas Krogull -- The use of priming in language attitudes research / Abby Walker, Katie Drager, and Jennifer Hay -- Mixed-methods approaches to the study of language attitudes / Ruth Kircher and James Hawkey.
Includes bibliographical references and index.
Keywords: Language awareness; Sociolinguistics; Language and languages -- Variation; Linguistics -- Research -- Methodology